ANALISIS NILAI-NILAI PENDIDIKAN KELUARGA DALAM AL-QUR'AN DAN RELEVANSINYA ATAS MARAKNYA ISU GLOBAL: ANALISIS NILAI-NILAI PENDIDIKAN KELUARGA DALAM AL-QUR'AN DAN RELEVANSINYA ATAS MARAKNYA ISU GLOBAL - Moh. Muttaqin; Muhid (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
Family education based on Qur'anic values plays a crucial role in shaping children's character andpersonality, especially in facing the increasingly complex challenges and global issues. TheQur'an, as a guidebook for life, provides clear directions on how families can educate their childrenwith strong religious values, while also shaping noble character that can be applied in daily life.This article aims to analyze the educational values in the Qur'an and their relevance to the widespread global issues, as well as how these values can be implemented in family education.This discussion includes several important values in the Qur'an such as piety, affection, effectivecommunication, worship, and noble character, all of which have a significant impact on shapingchildren's character. In conclusion, the implementation of Qur'anic values in family education notonly creates individuals with noble character but also shapes a better society capable of facingglobal challenges.